Design of Covid-19 Vaccination Education Social Campaign in Padang City in Motion Graphic - M. Sayuti; SettingsSyafira Ayunda; Riki Iskandar; Robby Usman (fakultas Desain Komunikasi Visual, 2025)
The current COVID-19 vaccination is needed which aims to increase thebody's resistance to avoid the dangers of COVID-19. Therefore, it is important to design social education campaigns to provide an overview to the public about COVID-19 and about COVID-19 vaccination. In this design there are five materials that will be conveyed to the public using interesting and easy-to- understand information. Researched using quantitative methods including conducting observations, interviews, literature studies and documentation as well as data analysis methods using SWOT. Among them Strength (strength), Weakness (Weakness), Opportunity (opportunity) and Threat (threat). Made in motion graphic videos that are interesting and provide clear information for the public to watch. And coupled with supporting media that can help get information from the main media such as posters, X-banners, billboards, brochures, t-shirts, handsanitizers, tumblers, mugs, paper bags, wall clocks, notebooks, stickers and also one of the social media such as YouTube.